INTERNALISASI NILAI TAUHID DALAM PEMBELAJARAN UNTUK MENINGKATKAN KEIMANAN MAHASISWA PROGRAM STUDI HUKUM KELUARGA ISLAM UIN SUNAN KALIJAGA - TAMIYA, ILFIKROTUT; Arif, Mahmud; Baidi, Yasin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2024)
This research aims to determine the role of monotheism learning on the behavior of students in the Islamic Family Law study program at Uin Sunan Kalijaga. This research is qualitative in nature and the materials used in the research come from primary data and secondary data which includes interviews and books and scientific articles related to the research. The results of the analysis show that learning monotheism is very important to apply in education, especially for students majoring in IPR Semester 3 at UIN Sunan Kalijaga, because with monotheism learning students can better know who their God is and make prophets or messengers of Allah role models so that they emulate the good behavior of the prophet. Allah so that student behavior will be better because they understand the concept of divinity and His various attributes. Apart from that, by learning monotheism, students will also be more obedient in carrying out Allah's commands and stay away from Allah's prohibitions, which can make them students who are knowledgeable, have good morals, and become obedient servants of Allah SWT.